Strategi Manajemen Konflik dalam Tim Multigenerasi di Lingkungan Kerja - Manalu, Gibson (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
Research on conflict management in multigenerational teams was conducted based on the phenomenon of increasing age diversity of employees in a company. This study aims to analyze: 1) factors causing conflict in multigenerational teams in the work environment, and 2) conflict management strategies to increase work productivity in multigenerational teams. The research method uses a descriptive qualitative approach through literature study. The analysis results show that the factors causing conflict in multigenerational teams include: differences in communication patterns, work methods, technology adaptation, and time management. Applicable conflict management strategies include: developing transparent communication between multigenerational employees, optimizing the advantages of each generation, identifying employee limitations, and implementing responsive leadership in managing multigenerational team dynamics. The research findings provide a foundation for developing effective conflict management strategies in work environments with generational diversity.